Research of the efficiency of the use of innovative resources organizations in Belarus - Kolesnikova, Irina I. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The ultimate goal of the study is to analyze the performance indicators of innovative resources of industrial organizations using economic and statistical methods. The proposed system of innovation resource performance indicators characterizes the performance of organizations from the standpoint of different input vectors: the indicators express the financial performance of organizations, the effectiveness of research and development, the cost effectiveness, the provision of fixed assets to workers, and the efficiency of labor input. As a result of the analysis, the growth of financial profitability of scientific and technical works was revealed; it characterizes a higher financial performance of research and development in comparison with the efficiency of sales of organizations. The structure of employment of scientific researchers in OECD countries is considered. As the share of expenditures on education in the total amount of expenditures of the consolidated budget decreases, it is necessary to create material incentives for attracting employees and securing the existing employment in the sphere of education. An international comparison of the share of government R&D expenditures in GDP by countries of the world was carried out, and countries with high and low levels of knowledge intensity were identified. It has been revealed that investments in fixed assets have a significant impact on the level of costs for technological innovations. Thus, the system of indicators allows us to understand the size of the research and development sector in the scale of the country’s economy.

Celem opracowania jest ocena wydajności innowacyjnych zasobów organizacji przemysłowych przy użyciu metod ekonomicznych i statystycznych. Analizowany system wskaźników efektywności wykorzystania zasobów innowacyjnych charakteryzuje wydajność organizacji z punktu widzenia różnych wektorów wejściowych: wskaźniki wyrażają wyniki finansowe organizacji, skuteczność prac badawczo-rozwojowych, efektywność kosztową, wyposażenie w środki trwałe (techniczne uzbrojenie pracy) oraz wydajność pracy. Wyniki analizy wskazują na wzrost rentowności finansowej prac naukowo-technicznych – badania i rozwój cechują się wyższymi wynikami finansowymi w porównaniu z efektywnością sprzedaży organizacji. W opracowaniu analizie została poddana ponadto struktura zatrudnienia naukowców w krajach OECD. Ustalono, że zmniejsza się udział wydatków na edukację w łącznej kwocie wydatków skonsolidowanego budżetu. Wskazano, że konieczne jest zapewnienie bodźców materialnych przyciągających wykwalifikowany personel do sektora edukacyjnego. Przeprowadzono także międzynarodowe porównanie udziału wydatków rządowych na badania i rozwój w PKB według krajów oraz zidentyfikowano kraje o wysokim i niskim poziomie intensywności wiedzy. Wykazano, że inwestycje w środki trwałe mają znaczący wpływ na poziom kosztów innowacji technologicznych. Rezultaty analiz są podstawą do wnioskowania, że rozważany system wskaźników pozwala ocenić kondycję sektora badawczo-rozwojowego w skali całej gospodarki narodowej
Keywords: innovative resources; financial efficiency; research intensity; funding for research and development; zasoby innowacyjne; efektywność finansowa; intensywność nauki; finansowanie badań i rozwoju